Domain decomposition method for solving incompressible fluid flow and energy equations using distributed parallel computer system - Manshoor, Bukhari

(untitled)
This paper is concerned with the development of an efficient scheme for solving the finite difference Navier-Stokes and energy equations using distributed parallel computer system. The numerical procedure is based on SIMPLE (Semi Implicit Method for Pressure Link Equations) developed by Spalding. The governing equations are transformed into finite difference forms using the control volume approach. The hybrid scheme which is combination of the central difference and up wind scheme is used in obtaining a profile assumption for parameter variations between the grids points. Parallelization method used on this distributed parallel computer system is Domain Decomposition Method (DDM). The accuracy of the parallelization method is done by comparing with a benchmark solution of a standardized problem related to the two dimensional buoyancy flow in a square enclosure. The results shown that the distributed parallel computer system will reduced an execution time to solve the problem about 70% compared to the serial computer.